ON THE ISSUE OF CONFLICT OF INTEREST IN CORPORATE RELATIONS - Kamalov, Mansurxon (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article explores the issue of conflicts of interest in corporate relationships arising between various participants in company management, such as owners, management, shareholders, and external stakeholders. It examines the causes and consequences of conflicts of interest, their impact on the effectiveness of corporate governance, and the legal mechanisms for their resolution. Using a real-life example, the article demonstrates how misalignment of interests between owners and management can lead to negative outcomes for a business. It also analyzes the fiduciary duties of managers and their role in preventing conflicts of interest. The article concludes with recommendations for improving internal and external control mechanisms and enhancing corporate culture to mitigate the risk of conflicts.